Skin cancer and DNA mutation due to ultraviolet radiation - Dinle, Leila Yusuf Hussein; Zhang, Ya Qin (International Journal of Research in Dermatology, 2022)
Ultraviolet (UV) radiation is emitted by the Sun as well as man-made sources such as tanning beds and welding torches. The process of energy being emitted from any source is known as radiation which can take many different forms, from extremely high-energy radiation like X-rays and gamma rays to extremely low-energy radiation like radio waves. UV photons are in the middle of the electromagnetic spectrum. They have higher energy than visible light but a lower energy than X-rays. It is divided into numerous groups based on the amount of energy they contain. Higher-energy UV photons are included in ionizing radiation, which means they have enough energy to ionize an atom or molecule. Ionizing radiation can cause cancer by damaging a cell’s DNA; however, it doesn’t have enough energy to penetrate deep into the body, thus it mainly effects the skin only. UV radiations are considered the most carcinogenic factors which leads to skin cancer. Over 50 million each year is estimated to treat the melanoma skin cancer, but the incidences kept rising each year. The tanning and pigmentation in the skin are the main factors to develop skin cancer that rise concerns about ozone depletion. Continuing research should contribute to an improved knowledge of the genetic and immune suppressive mechanisms involved in the role of the tumor suppressor. Research into skin cancer may help raise consciousness about the harmful effects of UV which leads to improved methods of prevention and treatment of skin cancer.